Neonatal necrotizing enterocolitis in E. Rebagliati M. National Hospital: 1984-1988 - Oliveros Donohue, Miguel (1989)
This report presents 16 cases of neonatal necrotizing enterocolitis NEC). We reviewed the clinical picture and the laboratory results of our patients. According to the presentation time we divided our series in early and late variety, as in the literature previously reported. The risk factors were gestational age of 35 weeks or less, birth weight under 1500 g, low Apgar score, hematocrit higher than 65%, early artificial feeding, umbilical vessels' catheterization and abnormal intestinal colonization with pathogen germs. We consider very valuable serial abdominal X ray pictures and paracentesis for the diagnosis of chirurgic acute abdomen. (An Fac Med UNMSM 11 Epoca 1989; 1 (1-2): 15-18).